The effect of ambiguous visual stimuli on creativity in design idea generation. Issue 1 (3rd April 2019) - Jang, Sun Hee; Oh, Byungkeun; Hong, Sukil; Kim, Jinwoo
ABSTRACT: The purpose of the present study is to investigate the effect of visual stimuli on creativity for generating ideas among designers. A survey with design students was conducted in this investigation to extract visual stimuli from the sub-symbolic domain (vague stimuli), visual stimuli from the symbolic domain (definite stimuli), and visual stimuli between the two domains (ambiguous stimuli). Subsequently, a conceptual combination experiment was conducted using selected stimuli to examine the effects of ambiguous visual stimuli on creativity to generate ideas among designers. The results suggest that in individual working environments, dissimilar concept pairs fostered higher elaboration when ambiguous stimuli were present, whereas similar concept pairs fostered higher elaboration when vague stimuli were presented. It was further suggested that in group working environments, vague stimuli result in higher abstractness when dissimilar concept pairs are used, whereas ambiguous stimuli result in higher abstractness when similar concept pairs were used.